Tourism development strategy based on edutourism integrated with local wisdom: A case study of Gondanglor Lamongan - Ilmayasinta, Nur; Rochmatin , Ulifatur; Ambarwati, Dian Novi; Muflikhah, Luluk (Bahasa Indonesia, 2025)
Gondanglor Sugio Village has great potential to become a tourist village in Lamongan. Some of the tourist attractions in Gondanglor Village are Gondang Reservoir, G-Park, and Pesarean Nyai Dewi Sekardadu. But in reality, the number of tourists in Gondanglor village is decreasing every year. The aim of this research is to analyze the factors for the decline in the number of tourists and provide a policy brief for tourism development in Gondanglor Village. This research is qualitative research with a case study approach. Data obtained using interviews, questionnaires, observations and surveys. The results of the research show that one of the factors in the decline in the number of tourists is the strategy for optimizing the tourism management system which is less than optimal. This is demonstrated by management, planning, implementation of maintenance of tourist destinations, supervision, accessibility to tourist destinations, organization that only involves related agencies, and should be able to involve all stakeholders so that the involvement of all stakeholders in management can be optimal.